solve the given equations using exact differential
equations.
6. (cos x ∙ cos y − cot x)dx − (sin x ∙ sin y)dy = 0
7. x(3xy − 4y3 + 6)dx + (x3 − 6x2y2 − 1)dy = 0, when x = 2, y = 0
8. 2xydx + (y2 + x2)dy = 0
9. (xy2 + y − x)dx + x(xy + 1)dy = 0, when x = 1, y = 1
|10. (1 − xy)−2dx + [y2 + x2(1 − xy)−2]dy = 0, when x = 3, y = 4
"\\displaystyle\n(\\cos x. \\cos y- \\cot x)dx - (\\sin x \\sin y)dy= 0\\\\\n\\text{Let $M = \\cos x. \\cos y- \\cot x$ and $N = -\\sin x \\sin y$}\\\\\n\\text{Let $F(x,y) = \\int (-\\sin x \\sin y)dy$}\\\\\n\\implies F(x,y) = \\sin x \\cos y + h(y)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\n\\cos x \\cos y +h'(x) = \\cos x \\cos y -\\cot x\\\\\n\\implies h'(x) = -\\cot x\\\\\nh(x) = -\\ln \\sin x\\\\\n\\therefore F(x,y) = \\sin x \\cos y -\\ln \\sin x\\\\\n\\text{The solution to the exact differential equation is}\\\\\n\\sin x \\cos y -\\ln \\sin x=c\\\\\n2. \n(3x^2y-4y^3+6)dx - (x^3-6x^2y^2-1)dy= 0\\\\\n\\text{Let $M = 3x^2y-4y^3+6$ and $N = x^3-6x^2y^2-1$}\\\\\n\\text{Let $F(x,y) = \\int (x^3-6x^2y^2-1)dy$}\\\\\n\\implies F(x,y) = x^3y-2x^2y^3-y + h(y)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\n3x^2y-4y^3+h'(x) = 3x^2y-4y^3+6\\\\\n\\implies h'(x) = 6\\\\\nh(x) = 6x\\\\\n\\therefore F(x,y) = x^3y-2x^2y^3-y +6x\\\\\n\\text{The solution to the exact differential equation is}\\\\\nx^3y-2x^2y^3-y +6x=c\\\\\n\\text{When x = 2, y=0, hence c = 12}\\\\\n\\implies x^3y-2x^2y^3-y +6x=12\n3.\n(2xy)dx - (y^2+x^2)dy= 0\\\\\n\\text{Let $M = 2xy$ and $N = y^2+x^2$}\\\\\n\\text{Let $F(x,y) = \\int (y^2+x^2)dy$}\\\\\n\\implies F(x,y) = \\frac{y^3}{3}+x^2y + h(x)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\n2xy +h'(x) = 2xy\\\\\n\\implies h'(x) = 0\\\\\nh(x) = c\\\\\n\\therefore F(x,y) = \\frac{y^3}{3}+x^2y+c\\\\\n\\text{The solution to the exact differential equation is}\\\\\n\\frac{y^3}{3}+x^2y+c=c\\\\\n\\implies \\frac{y^3}{3}+x^2y+c=0\n4.\n(xy^2+y-x)dx - (x^2y+x)dy= 0\\\\\n\\text{Let $M = xy^2+y-x$ and $N = x^2y+x$}\\\\\n\\text{Let $F(x,y) = \\int (x^2y+x)dy$}\\\\\n\\implies F(x,y) = \\frac{x^2y^2}{2}+xy + h(x)\\\\\n\\text{Differentiating and equating it to M, we have}\\\\\nxy^2+y+h'(x) = xy^2+y-x\\\\\n\\implies h'(x) = -x\\\\\nh(x) = -\\frac{x^2}{2}\\\\\n\\therefore F(x,y) = x^3y-2x^2y^3-y +6x\\\\\n\\text{The solution to the exact differential equation is}\\\\\n\\frac{x^2y^2}{2}+xy-\\frac{x^2}{2}=c\\\\\n\\text{When x = 1, y=1, hence c = 1}\\\\\n\\implies \\frac{x^2y^2}{2}+xy-\\frac{x^2}{2}=1\\\\\n5. \n(1-xy-2)dx + (y^2+x^2-x^3y-2)dy\\\\\n\\text{The equation isn't exact as}\\\\\nM_y =-x, N_x=2x-3x^2y\\\\\nM_y \\neq N_x"
Comments
Leave a comment